Exploring Global Dynamics in Reading Literacy Research: A Bibliometric and Science Mapping Approach in Primary School Contexts - Nurmansyah, Gupi Rohman; Heryani, Rina (International Conference on Elementary Education, 2025)
This study aims to map reading literacy research in the context of primary school through a bibliometric approach. The analysis and interpretation in this study used data from Scopus. Our data is focused from 2014 to 2024 by including the keywords reading literacy, primary school and elementary school. VosViewer software is used to map and identify publication trends, author collaborations,clusters and thematic keywords. This study’s outcomes reveal that South African countries, Germany, the Russian Federation, Indonesia, China, Hong Kong, Taiwan, Slovenia, Australia and Norway are the most contributors to the theme of this study. Meanwhile, many authors have not recollaborated across regions and the theme of this research is still dominated in the scientific field of social science. Keywords such as mixed method, communicative competence, metacognition, reading fluency and project-based learning are potential words that are still rarely explored. These keywords are future research opportunities for the theme of reading literacy research in elementary schools.